Aesthetics of Prajuritan Dance in Semarang Regency - Jazuli, Muhammad (Harmonia: Journal of Arts Research and Education, 2015)
The scarcity of aesthetic study of traditional arts has evoked my intention to promote a model of aesthetic study in dance performance. The focus of this research is the aesthetics of Prajuritan dance in SemarangÂ  regency. The aesthetics were founded on dance choreography and cultural value systems, which grow and develop in the community of Semarang regency. Dances choreography includes dance background, form, shape, theme, number and formation of dancers, moves, musical accompaniment, make-up and costume, and dance floor patterns. Cultural value systems include communicating stories, expressed symbols, function and meaning of Prajuritan dance for its supporting community. The stories were derived from the heroic tale of Prince Sambernyawa (KGPAA, king Mangkunegara I in Mangkunagaran royal palace, Surakarta) when he rebelled against the arbitrary Dutch colonialists, with his famous spell, âtiji tibeh (mukti siji mukti kabeh â being prosperous for one and all)â and Three Dharma of soldiers, namely ârumangsa melu handarbeni, melu hangrungkebi, mulat sarisa hangrasa wani, which means having sense of belonging, protection, and awareness to bravely do whatever to defendÂ  his nation and country. Therefore, Prajuritan dance brings the mission to evoke sense of courage, discipline, and responsibility for the young generation.Â  Â Â